Changes in digital business model types - a longitudinal trend study of the United States fintech industry - Eckert, Constantin Johannes (2022)
The finance sector is undergoing significant changes that are enabling several new digital business models. Fintech start ups are expanding in new fields using new platforms to deliver better and more personalized services. Despite growing investments, the fintech movement still currently lacks some scientific understanding. Therefore, with this research, the goal is to extend the understanding through a longitudinal trend study of the business model types of fintech’s. This was done by analyzing how the business model types of newly founded start ups in the last decade have changed compared to those found earlier. Results have shown that Investing & Personal Finance (e.g., Robinhood), Infrastructure & Automation (e.g., Alloy), Digital Banking (e.g., Chime), and Cryptocurrency (e.g., Coin base) have increased significantly. In contrast, Finance & Analytics, Wealth Management, Real Estate & Mortgage, Payments & Payroll, and Lending have all decreased, with only Insurance increasing marginally.